Endoscopic removal of over-the-scope clips: Clinical experience with a bipolar cutting device. Issue 4 (June 2017) - Bauder, Markus; Meier, Benjamin; Caca, Karel; Schmidt, Arthur
Background: Over-the-scope clips (OTSCs) are increasingly used for the closure of perforations/fistulae, hemostasis and endoscopic full-thickness resection (FTRD system). When OTSC-associated complications occur or re-therapy at the OTSC site is needed, OTSC removal may be indicated. An experimental study in an animal model and a case series have shown good results for OTSC removal with a bipolar cutting device. We present a larger clinical study using this device. Methods: Data of all consecutive patients with indication for OTSC removal were collected and analyzed retrospectively. OTSCs were cut at two opposing sites using a bipolar grasping device to apply short direct current impulses. OTSC fragments were extracted with a standard forceps and a cap at the tip of the endoscope to avoid tissue damage. Results: Between December 2012 and February 2016 a total of 42 OTSC removals in the upper ( n  = 25) and lower ( n  = 17) gastrointestinal tract have been performed at our department. Overall technical success, defined as cutting the OTSC at two opposing sites and extraction of both fragments, was achieved in 92.9% (39/42) of all cases. Successful fragmentation of the OTSC was achieved in 97.6% (41/42). Minor bleedings were rare and could be managed endoscopically in all cases. There were no perforations and no major or delayed bleedings. Conclusion: Endoscopic OTSC removal with a bipolar cutting device is feasible, effective and safe. This technique can be applied in the upper and lower gastrointestinal tract.